Unification of large-scale laboratory rainfall erosion testing - Robeson, Michael D., author; Thornton, Christopher I., advisor; Abt, Steven R., committee member; Watson, Chester C., committee member; Williams, John D., committee member (Colorado State University. Libraries, 2014)
Water pollution degrades surface waters making them unsafe for drinking, fishing, swimming, and other activities. The movement of sediment and pollutants carried by sediment over land surfaces and into water bodies is of increasing concern with regards to clean waters, pollution control, and environmental protection. Due to increasing environmental concerns about sediment in water bodies derived from construction sites, along with increasingly stringent United States Environmental Protection Agency (USEPA) regulations, it is imperative to be able to have a uniform means to compute soil loss determined at large-scale laboratory rainfall-induced erosion facilities that can eventually be applied to construction sites. This dissertation utilized bare-soil data from the most commonly-utilized large-scale rainfall testing laboratories in the erosion-control industry to develop a unifying prediction equation that can be utilized to provide a proper foundation for determining design parameters to meet USEPA stabilization requirements. The developed equation was determined to be a function of the following key parameters: rainfall intensity, plot area, duration, slope gradient, median raindrop size, raindrop kinetic energy, percentage of clay in the soil, and compacted soil percentage. The developed equation for the prediction of rainfall-induced soil loss, developed from sixty-eight data points collected for this study, had a coefficient of determination (R2) of 0.88. The prediction equation unifies large-scale laboratory rainfall erosion testing and provides a means to determine the appropriate design parameters for USEPA stabilization requirements.
Keywords: testing; erosion; laboratory; rainfall